2019
DOI: 10.5194/acp-19-12083-2019
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cycle of short-term fluctuations of integrated water vapour above Switzerland

Abstract: Abstract. The TROpospheric WAter RAdiometer (TROWARA) continuously measures integrated water vapour (IWV) with a time resolution of 6 s at Bern in Switzerland. During summer, we often see that IWV has temporal fluctuations during daytime, while the nighttime data are without fluctuations. The data analysis is focused on the year 2010, where TROWARA has a good data quality without data gaps. We derive the spectrum of the IWV fluctuations in the period range from about 1 to 100 min. The FFT spectrum with a windo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…R 2 and RMSE verifications of the Opa-RR estimation at 21 GHz are 0.43 (0.39) and 7.83 (6.75) mm/day, respectively. This is not surprising because the sensor at 31 GHz is less sensitive to water vapor than at 21 GHz [12]. Another finding worth noting in Figure 4 is that the daily rain rate using Opa-RR is significantly lower than rain gauges when rain rates are between 20 mm/day and 50 mm/day (heavy rain), since the linear regression fit line is located below the x = y line.…”
Section: Daily Rain-rate Estimationmentioning
confidence: 87%
See 3 more Smart Citations
“…R 2 and RMSE verifications of the Opa-RR estimation at 21 GHz are 0.43 (0.39) and 7.83 (6.75) mm/day, respectively. This is not surprising because the sensor at 31 GHz is less sensitive to water vapor than at 21 GHz [12]. Another finding worth noting in Figure 4 is that the daily rain rate using Opa-RR is significantly lower than rain gauges when rain rates are between 20 mm/day and 50 mm/day (heavy rain), since the linear regression fit line is located below the x = y line.…”
Section: Daily Rain-rate Estimationmentioning
confidence: 87%
“…R 2 and RMSE verifications of the Opa-RR estimation at 21 GHz are 0.43 (0.39) and 7.83 (6.75) mm/day, respectively. This is not surprising because the sensor at 31 GHz is less sensitive to water vapor than at 21 GHz [12]. Figure 4 shows the verification scatter plots of the daily rain rate estimated by Opa-RR, and the comparison between ERA5 and rain gauges.…”
Section: Daily Rain-rate Estimationmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, other factors than temperature might be responsible for IWV changes in winter, such as changes in dynamical patterns and the horizontal transport of humid air. Indeed, Hocke et al (2019) showed that evaporation of surface water plays a minor role in winter, with a latent heat flux that is in Bern six to seven times smaller than in summer, suggesting that horizontal transport of humid air is in winter more important than evaporation. We thus conclude that IWV in Bern changes as expected from temperature changes in early spring, late summer and autumn, but other processes might also be responsible for IWV changes, especially in winter.…”
Section: Changes In Iwv and Temperature Around Bernmentioning
confidence: 99%